Automatic battery module swapping station for autonomous mobile robots - Lim, Jun How (2024)
This report presents the design, development, and testing of an Automatic Battery Module Swapping Station and Lithium-Ion Battery Module. The primary objective was to create a system capable of efficiently replacing battery modules in an Automated Mobile Robot (AMR) environment. The Automatic Battery Module Swapping Station was constructed with key features, including a bi-directional belt conveyor, an exchange platform with a battery loading and unloading mechanism, and battery storage compartments. Testing revealed robust performance across individual subsystems and integrated components, with successful load-bearing tests and tilt angle validation. The Lithium-Ion Battery Module, comprising 3D-printed parts and electronic components, underwent extensive mechanical stress testing and functional evaluation, demonstrating structural integrity and effective communication capabilities. Conclusions highlight the successful achievement of project objectives, while recommendations for future work include scalability enhancements, predictive maintenance implementation, and mechanical safety improvements. Overall, this report provides valuable insights into the design and testing of battery swapping technology, paving the way for further advancements in automation and battery management systems.